2022
DOI: 10.1155/2022/5331537
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effects of Naringin in a Rat Model of Postoperative Intraperitoneal Adhesion Formation

Abstract: Background. Many attempts have been made to inhibit the formation of postoperative intraperitoneal adhesions, but the results have been discouraging. Therefore, the identification of effective preventative measures or treatments is of great importance. In this study, the substantial potential of naringin (NG) to reduce peritoneal adhesions was validated in a rat model. Materials and Methods. A rat peritoneal adhesion model was established by abrasion of the cecum and its opposite intraperitoneal region under a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In our study we superficially demonstrated that Houpu Paiqi mixture can promotes intestinal function recovery in clinical settings. Its main components are honokiol (Magnolia officinalis), naringin, and emodin [ 8 10 ]. Honokiol (HKL) is a bioactive compound extracted from several species of magnolia officinalis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study we superficially demonstrated that Houpu Paiqi mixture can promotes intestinal function recovery in clinical settings. Its main components are honokiol (Magnolia officinalis), naringin, and emodin [ 8 10 ]. Honokiol (HKL) is a bioactive compound extracted from several species of magnolia officinalis.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicine has long been recognized for its ability to aid in the recovery of intestinal function [ 7 ], with Houpu Paiqi mixture being widely utilized and resulting in positive outcomes. Previous studies have demonstrated that the key constituents of Houpu Paiqi mixture possess anti-inflammatory properties, reduce oxidative stress, enhance intestinal peristalsis, and minimize postoperative adhesion formation [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%